2001
DOI: 10.1073/pnas.261572998
|View full text |Cite
|
Sign up to set email alerts
|

Powerful and prolonged protection of human retinal pigment epithelial cells, keratinocytes, and mouse leukemia cells against oxidative damage: The indirect antioxidant effects of sulforaphane

Abstract: median effect plot ͉ tert-butylhydroperoxide ͉ peroxynitrite ͉ glutathione ͉ quinone reductase ͉ 4-hydroxynonenal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
119
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(133 citation statements)
references
References 34 publications
(35 reference statements)
12
119
1
Order By: Relevance
“…HaCaT keratinocytes were chosen to examine this possibility because NQO1 is induced in this cell line by treatment with sulforaphane (Sul) (34). Initial experiments indicated that transfection of HaCaT cells with FITCtagged oligonucleotides resulted in 60-70% of cells staining positively under fluorescence microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…HaCaT keratinocytes were chosen to examine this possibility because NQO1 is induced in this cell line by treatment with sulforaphane (Sul) (34). Initial experiments indicated that transfection of HaCaT cells with FITCtagged oligonucleotides resulted in 60-70% of cells staining positively under fluorescence microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…The current literature describes the importance of Nrf2 for cellular resistance to pro-oxidant molecules (H 2 O 2 , tBHQ, and peroxynitrite), oxidant-generating molecules (menadione), in vivo situations that potentiate ROS-mediated damage (hyperoxic lung injury), as well as cytotoxic molecules that are neutralized by GSH detoxification or glucuronidation (4-hydroxynonenal, acetaminophen) (Duffy et al, 1998;Chan and Kan, 1999;Gao et al, 2001;Cho et al, 2002). However, it remains to be determined whether Nrf2 can provide resistance to relatively ROSindependent forms of cell death (i.e., excitotoxicity).…”
Section: Discussionmentioning
confidence: 99%
“…Now, there are ϳ2 dozen known phase II enzyme genes, with more to be elucidated via current technologies . Sharing common regulatory pathways, these enzymes possess chemically versatile antioxidant properties and are inducible by various agents, including those found in a normal diet (Fahey et al, 1997;Gao et al, 2001). Treatment of mammalian cells with electrophilic agents provokes a cellular response leading to the coordinated transcription of phase II genes (Prestera et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Induction of the phase 2 response protects against reactive oxygen species (ROS) arising from exogenous oxidants and oxidative cycling in many cell lines, including ARPE-19 retinal pigment epithelial cells (26,27) and U937 leukemia cells (19). We examined this protection and its dependence on nrf2 gene function by measuring formation of fluorescent products from the oxidationsensitive dye 2Ј,7Ј-dichlorodihydrofluorescein diacetate (DCFH-DA) in RAW264.7 cells and peritoneal macrophages derived from WT and nrf2 Ϫ/Ϫ mice that were exposed to tert-butyl hydroperoxide ( Table 2).…”
Section: Protection Of Macrophages Against Oxidative Stress By Inducementioning
confidence: 99%